Emergence and clonal dissemination of KPC-2- and NDM-1-coharboring Citrobacter freundii in China with an IncR plasmid - Juanjuan Zhou; Minghui Zhen; Kaijie Gao; Lu Xu; Dongyu Zhang; Junmei Yang (Microbiology Spectrum)
ABSTRACT The rise of carbapenem-resistant Enterobacteriaceae coharboring KPC-2 and NDM-1 poses a significant public health threat. KPC-2-NDM-1-Citrobacter freundii is rarely reported in clinical settings. In this study, we report the largest cohort of eight KPC-2-NDM-1-C. freundii isolated from children with urinary tract infections. Comprehensive characterization, including antimicrobial susceptibility testing, plasmid conjugation, whole-genome sequencing, and comparative genomics, was conducted for these clinical strains. Antimicrobial susceptibility testing indicated that all strains were resistant to meropenem [minimal inhibitory concentration (MICs) ≥ 8 µg/mL] and imipenem (MICs > 8 µg/mL). Genotyping and comparative genomics analyses identified the eight KPC-2-NDM-1- C. freundii belonging to ST523, exhibiting a close relationship characterized by 45 single nucleotide polymorphisms. Whole-genome sequencing and plasmid analysis confirmed the presence of blaKPC-2 and blaNDM-1 on an IncR plasmid named pC275-2 with 46,050 bp. The blaNDM-1 was integrated within the blaNDM-1 related region, which includes ΔISAba125, blaNDM-1, ble-MBL, trpF, dsbD, and ISCR1, while the blaKPC-2 gene was located on a novel non-Tn4401 genetic element. The blaKPC-2 genetic architectures containing blaKPC-2 differed from classical structures, underscoring the ongoing evolution of these genetic elements.IMPORTANCEOur study described the largest cohort to date of eight ST523 KPC-2-NDM-1-C. freundii isolated from children with urinary tract infections. The cooccurrence of KPC-2, a serine β-lactamases, and NDM-1, a metallo-β-lactamase on an IncR plasmid pC275-2 from a clinical carbapenem-resistant C. freundii. The conserved insertion structure mediated the blaNDM-1, and the propagation of blaKPC-2 gene with a new genetic background using IncR plasmid in clinical settings promotes the emergence of superbugs necessitating vigilant monitoring. Our research detected that ST523 KPC-2- NDM-1-C. freundii were disseminated in a children’s hospital. The potential spread of an IncR plasmid within the hospital raises concerns about the pandemic potential of this clone that produces two carbapenemases: KPC-2 and NDM-1. Further investigations will be necessary to control and prevent the spread of KPC-2-NDM-1-C. freundiis.